Environmental injustice and mobility impairment - Cahill, Michael (Trabajo Social Global-Global Social Work, 2013)
The study of mobility is a growth area in the social sciences. The car system (automobility) has hadas one of its consequences reduced opportunities for mobility impaired people to walk in their localenvironment. Immobility has resulted for many people with disabilities. Despite the promotion ofphysical activity by public health guidance local environments are often hazardous for mobilityimpaired people. In particular, there is a problem with cars parking on pavements and pavementcycling.